Influence of titania nanotubes diameter on its antibacterial efficacy against periodontal pathogens: An In vitro analysis - S Raja Rajeswari; Vidyashree Nandini; Agilan Perumal; Rajendran; Triveni Gowda (Wolters Kluwer Medknow Publications, 2021)
Background: Peri implant infection in dental implantology is a frequently encountered clinical problem. Titania nanotubes (TNTs) are recent improvement in surface characterization, showing promising results. Aim: The nanosurface parameter tweaking has been implicated with profound change in the microbiological and biological response. Hence, it was proposed that alteration in the nanotube diameter could have positive influence in its antibacterial activity against salient periodontal pathogens. Materials and Methods: Commercially, pure titanium discs of 8-mm diameter and 1.5-mm thickness were prepared. Polished titanium discs were used as control (Group A). Vertically oriented, structured TNTs were fabricated by anodization technique and grouped as B and C, having nanotube diameter, 40 and 80 nm subsequently. The surface characterizations of the samples were done by scanning electron microscope analysis. The antibacterial activity was evaluated with the bacterial colony counting method, at 24 h, 72 h, and 1-week intervals. Statistical Analysis: The one-way analysis of variance and Tukey's honest significance post hoc test were employed to assess the statistical significance. Results: The 80 nm nanotubes showed better antibacterial activity comparatively, at all three-time intervals investigated. Conclusion: The optimal TNT diameter of 80 nm was the most effective from an antimicrobial stand point of view.